Peningkatan Aksesibilitas dan Identitas Rumah Warga Melalui Program Pemasangan Nomor Rumah oleh Mahasiswa KKN di Desa Toto Projo Kecamatan Way Bungur - Syhan Rafif Fathana Bimbo; Sefia Kurniasari; Salsabila Salsabila; Muhammad Wahyu Rayhan; Soni Andriyansyah; Shela Sabrina; Shila Aprilia; Salsabilla Ayyu Khofiffa; Septiara Latifah Cahya Ningtias; Nuryanto Nuryanto; Selin Jurniasari (DEDIKASI: Jurnal Pengabdian kepada Masyarakat, 2026)
The house numbering program implemented by Community Service (KKN) students in Toto Projo Village, Way Bungur District, East Lampung Regency, aimed to improve accessibility, orderliness, and residential identity. Preliminary observations revealed that the majority of houses in the village lacked clear numbering systems, creating difficulties in population data collection, emergency services, social assistance distribution, and geographic navigation. The implementation method employed a participatory approach involving village government, village officials, and community members through stages of coordination, data collection, house number design, production, installation, and evaluation. Data were collected through direct observation, in-depth interviews, and documentation. Program results demonstrated that house numbering installation provided positive impacts in facilitating public service access, enhancing village administrative efficiency, and strengthening residential identity. Evaluation through interviews revealed high levels of resident satisfaction with the program, with particular appreciation for improved navigation and environmental orderliness. This program can serve as a sustainable community service model and be replicated in other villages with support from local government and integration of digital mapping technology to enhance spatial and demographic data management effectiveness.